Rick - Gino, Alex (New York : Scholastic Press, 2020)
Eleven-year-old Rick Ramsey has generally gone along with everybody, just not making waves, even though he is increasingly uncomfortable with his father's jokes about girls, and his best friend's explicit talk about sex. But now in middle school he discovers the Rainbow Spectrum club, where kids of many genders and identities can express themselves--and maybe among them he can find new friends and discover his own identity, which may just be to opt out of sex altogether.
School Library Journal starred, February 2020
Booklist starred, February 2020
Pub Weekly, February 2020
3-6
780L
5.1
Keywords: Identity (Psychology) -- Juvenile fiction; Sexual minorities -- Juvenile fiction; Asexual people -- Juvenile fiction; Middle schools -- Juvenile fiction; Friendship -- Juvenile fiction; Clubs -- Juvenile fiction; Identity -- Fiction; Sexual minorities -- Fiction; Asexual people -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Friendship -- Fiction; Clubs -- Fiction; LGBTQ+ fiction